Customer relationship management and organization performance among small and medium sized hotels in Langkawi - Lee, Choon Tong (2014)
Customer relationship and organization performance is an important issues among the small and medium size hotels in Langkawi. This is because customer is the main source of income for the organization. Therefore, organization requires seeking methods to improve the customer relationship since it can influence the organization performance. The purpose of this study was to investigate the relationship between customer relationship management and organization performance among small and medium size hotels in Langkawi. The sample of this study comprised of the 69 managers among the small and medium size hotels in Langkawi. In this study, questionnaire was used as instrument for data collection. In addition, regression and correlation analysis are used to analyze the correlation between independent variables and dependent variable. The research results have shown that the small and medium size hotels in Langkawi has high implementation in customer relationship management at current stage. Meanwhile, technology based CRM, CRM organization and customer orientation as dimensions of customer relationship management significantly influenced organization performance. However, only knowledge management is not significantly influenced organization performance. Besides, the study faced several limitations such as time and budget constraints which limited this study only to concentrate in Langkawi area. The findings of this study have some contributions for future research and organization performance development.